Key issues for bank-customer commitment and trust in an e-banking era - Laksamana, Patria; Wong, David; Kingshott, Russel; Muchtar, Fatimah (Electronic Business Management Society, 2011)
The competitive structure of the banking sector has evolved, and is now characterised by greater scope of competition from online banks, increased spatial distance brought about by the use of e-banking, a situation of near “perfect information” brought about by greater information sharing on web forums evaluating bank products, and a growing cohort of deal-oriented customers who may not want to be locked-in to any particular bank. While the constructs of commitment and trust have been widely applied in relationship marketing studies, the structural changes occurring in the banking sector have brought about the necessity of examining key issues that impact on long-term commitment in bank-customer relationships for the current context. Through solid fundamentals in social exchange theory and equity theory as well as logical arguments from previous research, we suggest examining the changing role of switching costs and social bonds in this new environment, and pose several questions that researchers need to address.